Elementary School Teachers' Enactment of a Content Literacy Curriculum in a Virtual Tutoring Program for Multilingual Students - Jackie E. Relyea; Dennis S. Davis; Sarah Dempsey Dawson; Corrie Dobis (MDPI AG, 2024)
This study evaluated the usability of a content literacy curriculum designed for graduate students' practicum experience in a virtual after-school tutoring program for U.S. third-grade multilingual students during the COVID-19 pandemic. We explored teacher perceptions of the successes and challenges encountered while implementing the curriculum. This study involved 12 elementary school teachers enrolled in a graduate school professional development program to fulfill their practicum requirements. The curriculum emphasized a thematic unit that utilized conceptually coherent texts across science and social studies, comprehension monitoring, academic vocabulary network building, and academic conversation. An analysis of teachers' written reflections revealed that a significant success was the enhancement of students' engagement in learning concepts and building vocabulary through high-interest informational texts. Teachers also recognized critical teaching moments that underscored the importance of developing interconnected knowledge structures for effective text comprehension and learning. However, the study identified a need for targeted and individualized scaffolding to support students with reading comprehension challenges, making complex texts more accessible. Additionally, the shift to remote teaching necessitated the development of a new pedagogical model for professional development to effectively address the evolving needs of teachers in virtual learning environments.